2000
DOI: 10.1111/j.1744-618x.2000.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Impaction: A Review

Abstract: TOPIC. Fecal impaction, a review of the literature. PURPOSE. To review the definition, diagnosis, causes, signs and symptoms, and treatment of fecal impaction. SOURCES. Published literature. CONCLUSIONS. While a great deal has been published on fecal impaction, there is limited research. Clarification of when constipation changes to impaction is ambiguous. Causes of fecal impaction are multiple, and people can be afected at all ages. Signs and symptoms of and problems associated with fecal impaction are varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Definition was review by Creason and Sparks [18] and among those definitions provided by the literature, we chose the more restrictive which, was considered appropriate by gastroenterologists and nursing homes’ doctors, according to the first part of the design of the questionnaire. Thus, faecal impaction was defined as an accumulation of hard faeces in the rectum that the subject was unable to evacuate themself, occurring at least once in the last year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition was review by Creason and Sparks [18] and among those definitions provided by the literature, we chose the more restrictive which, was considered appropriate by gastroenterologists and nursing homes’ doctors, according to the first part of the design of the questionnaire. Thus, faecal impaction was defined as an accumulation of hard faeces in the rectum that the subject was unable to evacuate themself, occurring at least once in the last year.…”
Section: Methodsmentioning
confidence: 99%
“…Faecal impaction occurs more frequently in the elderly [16,17], represents a relevant problem for caregivers, and it is potentially associated with complications [18], specially in patients with more than 80 years of age, or patients with heart or neurological disease [19]. Our knowledge of its epidemiology is limited, partly due to the inherent difficulties associated with conducting surveys in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…A study of geriatric wards in the United Kingdom showed that up to 42% of the old patients had fecal impaction 2. In some cases, it causes a serious situation; impaction of hard fecal mass on the colonic wall may cause stercoral ulcer, lower gastrointestinal bleeding,3 intussusception,4 or even perforation 5. For patients with fecal impactions, the aims of management are to relieve symptoms, clear out colon, and restore normal bowel habit.…”
Section: Discussionmentioning
confidence: 99%
“…1 Causes of fecal impaction include gender (women), socioeconomic status, low intake of dietary fiber, dehydration, immobility, alcohol ingestion, use of constipating drugs, hypothroidism. 2 She was under treatment of psychosis with Risperdal ® (risperidone) and Largactil ® (Chlorpromazine hydrochloride) for 15 years. The patient had tremors which is a known side effect of risperdal (Parkinson like effect).…”
Section: © Tkrcd 2011mentioning
confidence: 99%
“…1 Causes of fecal impaction include gender (women), socioeconomic status, low intake of dietary fiber, dehydration, immobility, alcohol ingestion, anti-psychosis drugs, hypothroidism. 2,3 In this report, we present a case with anti-psychosis treatment who had complications secondary to fecalith impaction and needed emergent laparotomy.…”
Section: Introductionmentioning
confidence: 99%